2021
DOI: 10.1109/access.2021.3051491
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Wormhole Attack Detection in Mobile Ad-Hoc Network (MANET)

Abstract: Mobile Ad-hoc Networks (MANET) are decentralized wireless networks that communicate without pre-existing infrastructure. MANETs are vulnerable to the most popular types of attacks and threats, such as wormhole attacks. A wormhole attacks is very challenging issues that records the packets from one location of the network and tunnels them to another location to undermines the performance of the wireless network and disrupt the most routing protocol. However, the existing solutions have been developed to overcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…When a malicious node receives an RREQ packet, it sends an RREP showing the shortest and fastest route to the intended destination. When a source node starts sending packets to a malicious node, it further sends to another distantly located wormhole node via a wormhole tunnel which may drop all the data packets and cause network interruption [6]- [8]. It can quickly be launched without having a knowledge network or compromising any legitimate nodes or cryptographic mechanism.…”
Section: Wormhole and Sinkhole Attacksmentioning
confidence: 99%
“…When a malicious node receives an RREQ packet, it sends an RREP showing the shortest and fastest route to the intended destination. When a source node starts sending packets to a malicious node, it further sends to another distantly located wormhole node via a wormhole tunnel which may drop all the data packets and cause network interruption [6]- [8]. It can quickly be launched without having a knowledge network or compromising any legitimate nodes or cryptographic mechanism.…”
Section: Wormhole and Sinkhole Attacksmentioning
confidence: 99%
“…They proposed a trust-based approach and tested performance based on different measures. The other hybrid attack scenario was proposed by Tahboush and Agoyi (30) and analyses its effect with and without detection algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…Route diversion attacks can also be in the shape of a wormhole attack in MANET. The recent work of Tahboush et al [14] has presented a security scheme using the round trip time to reduce delay and explore the tunnel presented by wormhole attack. The study outcome is found to stop both in-band and out-band attacks by wormhole attackers by controlling the transmission range.…”
Section: Review Of Literaturementioning
confidence: 99%